MICROCONTROLLER-BASED BIRD REPELLENT DEVICE AT THE AIRPORT: DESIGN, SENSOR, AND POWER SUPPLY - Ardia Chandra, Putu Wisnu; Racahyo, Rakha; Sunardi, Sunardi; Martadinata, M. Indra; Suprihartini, Yayuk (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2025)
The development of electronic technology as a control system has progressed rapidly in the era of society 5.0. Various facilities at the airport have implemented microcontrollers, especially bird repellent devices, to realize the concept of a smart airport. Bird repellent devices are designed to automatically and efficiently repel birds. This is because birds pose a threat to increasing the risk of bird strikes, which can cause damage to aircraft engines and trigger flight accidents. When designing bird repellent devices, researchers must consider the design, sensors, and power supply to enhance the effectiveness of the tool when applied in the field. This article will review the factors that influence the effectiveness of bird repellent devices, namely: design, sensors, and power supply, in a literature review. The purpose of this writing is to build a hypothesis of the influence of the design, sensor, and power supply used in the design of bird repellent devices so that it can be used as a reference in further research. The results of this literature review article are: 1) the design affects the bird repellent; 2) the sensor affects the bird repellent; and 3) the power supply affects the bird repellent.